Hindrances and outcomes of social bonding in exporter-importer relationships: The moderating role of formal contracting and ethical climate - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Christodoulides, Paul (My University, 2023)
Drawing on Transaction Cost theory, Relational Exchange theory, and Social Information Processing theory, we develop and test a conceptual model that investigates the damaging effect of certain key behavioral factors on social bonding between an exporter and its import buyer, and its subsequent impact on the exporting firm's long-term orientation in their working relationship. We also examine the moderating role of formal contracting and ethical climate governing this relationship. The model was tested with data collected from 262 Greek export manufacturers, using structural equation modeling. The results indicate that opportunism, distance, and conflict negatively affect social bonding in the working relationship between an exporter and its importer customer, which ultimately leads to detrimental effects on the exporting firm's long-term orientation. However, both the existence of formal contracting and the prevalence of a strong ethical climate were found to be responsible for alleviating the negative effect of most of the associations between inhibiting behavioral factors and social bonding.
Keywords: Business relationships; Ethical climate; Exporting; Formal contracting; Long-term orientation; Social bonding